Analysis of The Quality of Basic Pencak Silat Techniques in Pencak Silat Athletes of The Pamur Banyuwangi School, Srono Branch - Hervian Habib Hawe; Iman Imanudin; Unun Umaran (Universitas Negeri Semarang, 2025)
This study aims to analyze the quality of basic pencak silat techniques specifically straight punches, T-kicks, crescent kicks, and straight kicks among athletes of the PAMUR Banyuwangi Srono Branch. Employing a quantitative descriptive approach with a survey method, data were collected through a standardized skills test involving 22 active athletes. The assessment used the “Pencak Silat Skills Test for Students at faculty of sports science Universitas Negeri Yogyakarta” to measure technical execution within 20 seconds per movement. Results showed an average total score of 83.36, with a standard deviation of 10.47, indicating varied technical abilities among athletes. The classification revealed 36.4% of athletes were in the “good” category, 27.3% in both the “sufficient” and “lacking” categories, and 9.1% in the “very lacking” category. No athletes reached the “very good” category. These findings highlight that while most athletes perform at a moderate to good level, there is a clear need for structured coaching, regular evaluation, and individualized training programs. Coaches are advised to provide consistent feedback and develop techniques tailored to athletes’ capabilities to improve overall performance and mastery of basic pencak silat skills.